Disabling chronic low back pain as an iatrogenic disorder: a qualitative study in Aboriginal Australians. Issue 4 (9th April 2013) - Lin, Ivan B; O'Sullivan, Peter B; Coffin, Juli A; Mak, Donna B; Toussaint, Sandy; Straker, Leon M
Abstract : Objectives: To determine the low back pain beliefs of Aboriginal Australians; a population previously identified as protected against the disabling effects of low back pain due to cultural beliefs. Design: Qualitative study employing culturally appropriate methods within a clinical ethnographic framework. Setting: One rural and two remote towns in Western Australia. Participants: Thirty-two Aboriginal people with chronic low-back pain (CLBP; 21 men, 11 women). Participants included those who were highly, moderately and mildly disabled. Results: Most participants held biomedical beliefs about the cause of CLBP, attributing pain to structural/anatomical vulnerability of their spine. This belief was attributed to the advice from healthcare practitioners and the results of spinal radiological imaging. Negative causal beliefs and a pessimistic future outlook were more common among those who were more disabled. Conversely, those who were less disabled held more positive beliefs that did not originate from interactions with healthcare practitioners. Conclusions: Findings are consistent with research in other populations and support that disabling CLBP may be at least partly iatrogenic. This raises concerns for all populations exposed to Western biomedical approaches to examination and management of low back pain. The challenge for healthcare practitioners dealing with people with low back pain from any culture is to communicate in a way that builds positive beliefs about low back pain and its future consequences, enhancing resilience to disability.